Probing differential Ag+-nucleobase interactions with isothermal titration calorimetry (ITC): towards patterned DNA metallization - Shukla, Sourabh; Sastry, Murali (Nanoscale, 2009)
DNA has been Successfully used as a scaffold for the fabrication of metallic nanowires, primarily based oil the electrostatic complexation and reduction of the metal cations on the negatively charged sugar-phosphate backbone. Here. we probe the differential binding affinities of nucleobases for silver ions using sensitive isothermal titration calorimetry (ITC) measurements of the reaction enthalpies, which go in order: C > G > A >= T. Using the disparity between the interaction of cytosine (strong binding) and thymine (weak binding) with silver ions, we have successfully generated silver nanoparticle doublets and triplets on custom-made oligonucleotides, C-30-T-40-C-30 and C-20-T-20-C-20-T-20-C-20, respectively. Thus, it new and simple method of generating metallized DNA wires is presented, based entirely on the nucleotide sequence of DNA. The concept could be extended to other cations and complex DNA sequences in order to achieve intricately patterned DNA constructs.